Pulmonary Embolism Due to Protein S Deficiency in Pregnancy - Pek-Ha Mak; Ming-Kwang Shyu; Chien-Nan Lee; Fon-Jou Hsieh (Taiwanese Journal of Obstetrics & Gynecology, 2005)
Objective: Inherited thrombophilia is an uncommon disease that may cause recurrent thrombosis and may complicate pregnancy. A patient with protein S deficiency suffered antepartum deep venous thrombosis (DVT) and antepartum pulmonary embolism (PE) in the following pregnancy. She had both successful pregnancies managed by anticoagulant and close fetal surveillance. Case Report: A 28-year-old woman with protein S deficiency experienced an episode of DVT of the left lower extremity in her first pregnancy and an episode of PE in her second pregnancy. In both pregnancies, the venous thromboembolism (VTE) was treated successfully with low-molecular-weight heparin (LMWH). Conclusion: Prophylactic anticoagulant therapy should be administered throughout the antepartum and postpartum periods for pregnant women with inherited thrombophilia and a previously documented VTE. LMWH is the first-line drug of choice for both prophylaxis and treatment of VTE since it does not cross the placenta and is not teratogenic.